RATING CREATION FOR PROFESSIONAL EDUCATIONAL ORGANIZATIONS BASED ON THE ITEM RESPONSE THEORY - N. E. Erganova; L. V. Kolyasnikova (Образование и наука)
The aim of the investigation is to theoretically justify and describe approval of the measurement of the level of provision of educational services, education qualities and rating of vocational educational organizations.Methods. The fundamentals of methodology of the research conducted by authors are made by provisions of system approach; research on a schematization and modeling of pedagogical objects; the provision of the theory of measurement of latent variables. As the main methods of research the analysis, synthesis, the comparative analysis, statistical methods of processing of results of research are applied.Results. The paper gives a short comparative analysis of potentials of qualitative approach and strong points of the theory of latent variables in evaluating the quality of education and ratings of the investigated object. The technique of measurement of level of rendering educational services at creation of a rating of the professional educational organizations is stated.Scientific novelty. Pedagogical opportunities of the theory of measurement of latent variables are investigated; the principles of creation of ratings of the professional educational organizations are designated.Practical significance. The operational construct of the latent variable «quality of education» for the secondary professional education (SPE) approved in the Perm Territory which can form base of formation of similar constructs for creation of a rating of the professional educational organizations in other regions is developed.